A Case Report on Decompensated Chronic Liver Disease with Budd–Chiari Syndrome - Maharshi, Mallela; Thaneti, Joel Nathan; Jyothi, Padigala Ramya; Devi, A. G. N. Harshita; Deepa, Nani; Hemalatha, Ganjala; Kedareswari, Jonnadula; Paul, Nemalikanti Elizabeth Mary; Sathwika, Manchikanti Hima; Jirra, Vijaya Bhaskar (Journal of Pharmacy Practice and Community Medicine, 2026)
The rare illness, known as Budd-Chiari Syndrome (BCS), is characterized by hepatic venous outflow tract obstruction and can arise from the right atrium, inferior vena cava, or the tiny hepatic veins within the liver. It is an uncommon liver condition in which obstructions, typically caused by blood clots, restrict the hepatic veins, preventing blood from exiting the liver and returning to the heart. As a result, the liver enlarges (hepatomegaly), accumulates fluid (ascites), and causes abdominal pain. We present a rare case of a young female diagnosed with decompensated chronic liver disease secondary to Budd–Chiari syndrome, who came with the features of abdominal distension and weight loss, along with a Model for end stage liver disease Na score of 20 and splenomegaly with portal hypertension. The diagnosis was confirmed by Doppler ultrasonography and contrast-enhanced CT of the abdomen, supported by abnormal laboratory parameters including prolonged prothrombin time with elevated INR, decreased serum albumin and total protein levels, and elevated WBC count, lymphocytes, GGT, and bilirubin. Management included anticoagulants, antibiotics, statins, proton pump inhibitors, β blockers, hepatoprotective agents, diuretics, and other supportive care, with a step-up approach planned for hepatic venous outflow restoration to prevent disease progression.
Keywords: Budd-Chairi syndrome; Ascities; Hepatomegaly; Liver; Endoluminal venous lesion